Self-compassion influences PTSD symptoms in the process of change in trauma-focused cognitive-behavioral therapies: a study of within-person processes - Hoffart, Asle; Øktedalen, Tuva; Langkaas, Tomas F. (Frontiers in Psychology, 2015)
Abstract Although self-compassion is considered a promising change agent in the treatment of PTSD, no studies of this hypothesis exist. This study examined the within-person relationship of self-compassion components (self-kindness, common humanity, mindfulness, self-judgment, isolation, over-identification) and subsequent PTSD symptoms over the course of therapy. Method: PTSD patients (n = 65) were randomized to either standard prolonged exposure, which includes imaginal exposure (IE) to the traumatic memory, or modified prolonged exposure, where imagery re-scripting (IR) of the memory replaced IE as the imagery component of prolonged exposure in a 10 week residential program. They were assessed weekly on self-compassion and PTSD symptom measures. The centering method of detrending was used to separate the variance related to the within-person process of change over the course of treatment from between-person variance. Results: The self-compassion components self-kindness, self-judgment, isolation, and over-identification had a within-person effect on subsequent PTSD symptoms. These relationships were independent of therapy form. The within-person relationship between self-judgment and subsequent PTSD symptoms was stronger in patients with higher initial self-judgment. By contrast, there were few indications that within-person variations in PTSD symptoms predict subsequent self-compassion components. Conclusion: The results support the role of self-compassion components in maintaining PTSD and imply the recommendation to facilitate decrease of self-judgment, isolation, and over-identification and increase of self-kindness in the treatment of PTSD patients. The reduction of self-judgment appears to be most important, especially for patients with a high initial level of self-judgment.